Pemetaan Kompetensi Guru Paud di Kecamatan Selaparang Tahun 2024 - Andara, Mila; Karta, I Wayan; Gunawan, Gunawan; Nurhasanah, Nurhasanah (Indonesian Publication Center, 2024)
This research aims to map the competency of PAUD teachers in Selaparang sub-district in 2024. This research is a qualitative descriptive study. The population is 109 teachers. The sampling technique is proportionate quota sampling with specifications for educational qualifications, certification and school accreditation. The sample consisted of 72 teachers. Data analysis uses 4 stages of Miles and Huberman model analysis, namely data collection, data reduction, data presentation, drawing conclusions and calculating using a presentation formula. The results of research from 72 teachers in the Selaparang sub-district area are 18.06% of teachers' pedagogical competence is in the very good category, 33.33% of their personality competence is in the very good category, 6.94% of their professional competence is in the very good category, and social competence is in their very good category with a very good category of 22.22%. 30.65% of undergraduate PAUD qualifications are in the very good category, 14.2% of non-PG PAUD are in the very good category, 25.00% are certified in the very good category, 33.53% are A accredited schools in the very good category and 33.53% are accredited schools B with a very good category of 19.20%. Pedagogical, personality, professional and social competencies are on average in the good category. For educational qualifications, certification and school accreditation the average is in the good category. Therefore, it is hoped that the competent authorities will provide guidance so that teachers are in the very good category of at least 85%.